Assessment of laparoscopic skills of Gynecology and Obstetrics residents after a training program - Fernandes,Carla Ferreira Kikuchi (2016)
ABSTRACT Objective To evaluate laparoscopic skills of third-year Gynecology and Obstetrics residents after training at a training and surgical experimentation center. Methods Use of a prospective questionnaire analyzing demographic data, medical residency, skills, competences, and training in a box trainer and in pigs. Results After the training, there was significant improvement in laparoscopic skills according to the residents (before 1.3/after 2.7; p=0.000) and preceptors (before 2.1/after 4.8; p=0.000). There was also significant improvement in the feeling of competence in surgeries with level 1 and 2 of difficulty. All residents approved the training. Conclusion The training was distributed into 12 hours in the box trainer and 20 hours in animals, and led to better laparoscopic skills and a feeling of more surgical competence in laparoscopic surgery levels 1 and 2.